DIVERSI DALAM PENEGAKKAN HUKUM IN CONCRETO (PERSPEKTIF HUKUM PIDANA ISLAM) - Arafat, Muhammad; Tono, Sidik; Mulyaningsih, Rizki (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2024)
The enforcement of in concreto law refers to the practical implementation of law, transforming it from an abstract concept into a concrete application. Diversion, as an alternative resolution for juvenile cases outside the formal criminal justice system, aims to prevent stigmatization and allows children to reintegrate into their social environment in a balanced manner. This study employs a library research method with a juridical-normative approach, collecting data through documentation and analyzing it descriptively. The findings reveal that restorative justice and diversion focus on restoring losses suffered by victims, providing opportunities for offenders to participate in the recovery process, and involving the community in maintaining equitable peace. However, despite the extensive discussion of restorative justice and diversion in existing literature, there remains a gap in integrating Islamic legal principles, particularly As-sulh, into their application for juvenile cases. This raises two main questions: how can the concept of diversion be aligned with the principles of As-sulh to support the protection of children